Resistance training status and effectiveness of low frequency resistance training on upper-body strength and power in soccer players - Hertzog, M.; Rumpf, M. C.; Hader, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Soccer is classified as a contact/collision sport with many player-to-player duels. Winning these duels, shielding the ball or fending off an opponent requires upper-body strength and power. Therefore, the purpose of the study was, a) to examine upper-body strength and power changes in elite soccer players with different resistance-training (RT) status, b) to investigate if the RT status influences performances throughout an entire competitive season. Methods: Twenty-eight elite young male soccer players (age 18 ± 1 years, height 178 ± 5 cm, body mass 71 ± 7 kg) participated in this study and were divided into a trained (TG; n=14) and a novice (NG; n=14) group, according to their RT status (Rhea et al., 2003). Both groups performed the same upper-body RT once a week besides the soccer-specific team training over 30 weeks. Maximal strength was assessed via one repetition maximum (1RM) for bench press (BP) and bench row (BR) before (T1), after 10 weeks (T2) and the competitive season (T3). Maximal power (MP) was assessed in the BP exercise only. Results: At T1, TG presented significant and moderately greater 1RM in BP (+9.9 ± 10.2%; effect size, ES=1.0) and MP (+14.0 ± 13.1%; ES=1.1) than NG. There was no between-groups difference in 1RM for BR. At T2 and T3, both groups showed significant improvements in the 1RM. The magnitude of changes was small (TG; +5.9 ± 2.6%; ES=0.3-0.4) and large (NG; +11.7 ± 3.2%; ES=0.9-1.3) at T2 and increased to moderate (TG; +13.4 ± 3.1%; ES=0.7-0.9) and very large (NG, +20.6 ± 3.8%; ES=1.8-2.1) at T3. There is no change in MP at T2 and moderate improvement at T3 (+13.0 ± 5.8%; ES=1.1) for NG. TG presented a significantly small decrement at T2 (-11.6 ± 3.9%; ES=0.4) and small improvement at T3 (+7.7 ± 4.9%; ES=0.3). At T2 and T3, there was no between-groups difference in 1RM while MP remained moderately greater for TG. Discussion: The players with less RT experience presented a greater rate of improvement in maximal strength after 10 weeks only (Kraemer et al., 2004), notwithstanding a low RT frequency; while maximal power was not affected positively over the same time. One RT session per week is considered as an effective frequency for muscular strength and power maintenance (ACSM, 2009), however our results show that RT throughout a competitive season may elicit substantial improvement in upper-body maximal strength and power regardless of players` RT status.